„Obyś swoje dzieci uczył” – rodzice najmłodszych uczniów o edukacji zdalnej podczas pierwszej fazy pandemii COVID-19 - Dorota Zaworska-Nikoniuk (Problemy Wczesnej Edukacji)
In the conducted research, I was interested in the assessment of selected aspects of distance learning by parents of pupils in grades 1–3 of primary schools, on which I focused my attention in the undertaken research. Their aim was to diagnose the needs and expectations of parents regarding distance learning in the future, based on their experiences during the first phase of the COVID-19 pandemic. The research was conducted with the use of qualitative interviews conducted on 157 people, and supplemented by the analysis of the “Librus” distance learning reports. They showed that parents did not question the purposefulness of introducing distance learning model, but were critical of the forms of its administration, especially when lessons were not conducted online. Parents were very reluctant to send tasks to students via the Electronic Journal by teachers and the requirement to fill them in and send them back for evaluation. The teacher’s involvement in conducting online lessons, while activating students, was assessed positively. In the case of such young children, parents were disturbed by the lack of care in day-care centres, the closure of schools and the need to educate children at home.